Micro-Evolution Analysis Reveals Diverged Patterns of Polyol Transporters in Seven Gramineae Crops - Weilong Kong; Tong Sun; Chenhao Zhang; Yalin Qiang; Yangsheng Li (Frontiers in Genetics, 2020)
Polyol transporters (PLTs), also called polyol/monosaccharide transporters, is of significance in determining plant development and sugar transportation. However, the diverged evolutionary patterns of the PLT gene family in Gramineae crops are still unclear. Here a micro-evolution analysis was performed among the seven Gramineae representative crops using whole-genome sequences, i.e., Brachypodium distachyon (Bd), Hordeum vulgare (Hv), Oryza rufipogon (Or), Oryza sativa (Os), Sorghum bicolor (Sb), Setaria italica (Si), and Zea mays (Zm), leading to the identification of 12, 11, 12, 15, 20, 24, and 20 PLT genes, respectively. In this study, all PLT genes were divided into nine orthogroups (OGs). However, the number of PLT genes and the distribution of PLT OGs were not the same in these seven Gramineae species, and different OGs were also subject to different purification selection pressures. These results indicated that the PLT OGs of the PLT gene family have been expanded or lost unevenly in all tested species. Then, our results of gene duplication events confirmed that gene duplication events promoted the expansion of the PLT gene family in some Gramineous plants, namely, Bd, Or, Os, Si, Sb, and Zm, but the degree of gene family expansion, the type of PLT gene duplication, and the differentiation time of duplicate gene pairs varied greatly among these species. In addition, the sequence alignment and the internal repeat analysis of all PLTs protein sequences implied that the PLT protein sequences may originate from an internal repeat duplication of an ancestral six transmembrane helical units. Besides that, the protein motifs result highlighted that the PLT protein sequences were highly conserved, whereas the functional differentiation of the PLT genes was characterized by different gene structures, upstream elements, as well as co-expression analysis. The gene expression analysis of rice and maize showed that the PLT genes have a wide range of expression patterns, suggesting diverse biological functions. Taken together, our finding provided a perspective on the evolution differences and the functional characterizations of PLT genes in Gramineae representative crops.